2016
DOI: 10.1080/13543776.2016.1254193
|View full text |Cite
|
Sign up to set email alerts
|

2,2,2-Trifluoroethyl-thiadiazines: a patent evaluation of WO2016023927

Abstract: The Alzheimer's disease (AD) is acknowledged as the most common type of dementia in aging adults. It is characterized by the formation of intracellular neurofibrillary tangles and extracellular amyloid plaques. The latter insoluble deposits mainly consist of β-amyloid peptides (Aβ), which are the derivatives of the amyloid precursor protein (APP). The formation of neurotoxic Aβ-peptides involves the cleavage of APP with beta-secretase enzyme (beta-site APP cleaving enzyme 1, BACE1) so the potential of BACE1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Moreover, the construction of annulated ring systems is possible (Figure , top). Surprisingly, to date only a few cyclic sulfonimidamides have been reported . For example, research at Hoffmann-La Roche investigated six- and seven-membered cyclic or bicyclic sulfonimidamides as BACE1 inhibitors for potential treatment of Alzheimeŕs disease (Figure A). BASF Agrochemicals developed cyclic sulfonimidamide derivatives of the marketed insecticide sulfoxaflor with the aim to improve physicochemical properties and reduce toxicity in a series of pesticides (Figure B). , Further cyclic sulfonimidamides have been reported as bioisosters of carboxylic acids or sultams (Figure C).…”
mentioning
confidence: 99%
“…Moreover, the construction of annulated ring systems is possible (Figure , top). Surprisingly, to date only a few cyclic sulfonimidamides have been reported . For example, research at Hoffmann-La Roche investigated six- and seven-membered cyclic or bicyclic sulfonimidamides as BACE1 inhibitors for potential treatment of Alzheimeŕs disease (Figure A). BASF Agrochemicals developed cyclic sulfonimidamide derivatives of the marketed insecticide sulfoxaflor with the aim to improve physicochemical properties and reduce toxicity in a series of pesticides (Figure B). , Further cyclic sulfonimidamides have been reported as bioisosters of carboxylic acids or sultams (Figure C).…”
mentioning
confidence: 99%
“…[156][157][158][159][160][161] The search for new compounds in this series is due to the fact that tacrine, being one of the few drugs effi cient in the treatment and therapy of Alzheimer´s disease, has a pronounced hepatotoxic eff ect. 162 The reaction of ketones with 2-amino-3-cyanothiophenes is usually catalyzed by acids: TsOH and AlCl 3 , The Friedländer reaction takes place under a wide variety of conditions. Thus, thiophene 86 can react with The reaction of Gewald´s 2-aminothiophenes with ethyl acetoacetate is less unambiguous.…”
Section: Construction Of Thienopyridine System Through the Formation mentioning
confidence: 99%
“… Consequently, several programs have started focusing on devising new preparative approaches to such compounds and identifying new targets for unprecedented applications in various fields of research . Cyclic derivatives of sulfonimidamides have been recognized as three-dimensional heterocycles, contrasting their achiral sulfonamide-based analogues by the potential to obtain and apply single stereoisomers with stereogenic sulfur atoms. , The industrial interest in such compounds is revealed by the significant number of recent patents from pharmaceutical and crop protection companies Figure shows representative examples from our group with compound B being an acyclic N -acyl sulfonimidamide (and analogue of the anticancer agent tasisulam) and cyclic derivatives C and D with either one endo- and one exocyclic nitrogen substituent or two endocyclic nitrogens, respectively …”
mentioning
confidence: 99%